THE EVOLUTION OF PROGRAMMING LANGUAGES: A MULTINATIONAL ACADEMIC PERSPECTIVE (Наука и инновации, 2026)
This article examines the evolution of programming languages based on Uzbek and international academic sources. It describes the main stages of development, from machine language to modern high-level programming systems. The paper also discusses key programming paradigms such as procedural, object-oriented, and functional programming, and their role in software development. The study is based on qualitative analysis of scientific literature. The results show that programming languages have evolved toward greater abstraction, usability, and efficiency, and are now closely connected with modern technologies such as artificial intelligence and cloud computing.